Optimalisasi Kompetensi Mahasiswa Bidang Kewirausahaan Industri Olahraga Dalam Pemenuhan Misi Prodi PJKR FKIP UNTAD - Primadana, Ryo Sinung Primadana; Rivalwan; Moh. Tris Maulana Daipaha; Gustaman Candra Pardini (Program Studi Pendidikan Jasmani, Universitas Samudra, 2025)
This community service activity aims to optimise the entrepreneurial competencies of seventh-semester students in the Physical Education, Health, and Recreation (PJKR) Study Programme at the Faculty of Teacher Training and Education, Tadulako University, in facing the challenges of the growing sports industry. The implementation method involves five main stages: participant registration, distribution of interest and aptitude questionnaires, identification of training needs, conduct of training tailored to needs, and evaluation of activity outcomes. The programme focuses on massage training as a potential business venture selected based on questionnaire results. Training outcomes demonstrate a significant improvement in students' readiness to launch independent businesses in the sports industry. As many as 87% of participants felt more confident and had a clear vision of the business potential that could be developed. This activity also supports the mission of the PJKR programme in producing graduates who are adaptive, independent, and highly competitive in the creative economy sector based on sports.